Infraspecific variability of Amaranthus tricolor (Amaranthaceae) in India with a new variety - Das, Saubhik (Phytotaxa, 2013)
Amaranthus tricolor (Amaranthus subgen. Albersia sect. Pyxidium) is a native species of tropical Asia. It shows high inter- and intra-population phenotipic variability that is poorly known at present. During the field survey in India (West Bengal area) a large number of plants were collected and studied from the morphological point of view. The results justify the recognition of three varieties, of which one is new for the science: var. tricolor, var. tristis and var. acutus var. nov.